A Flexible TiO2(B)‐Based Battery Electrode with Superior Power Rate and Ultralong Cycle Life. (21st May 2013) - Liu, Shaohong; Wang, Zhiyu; Yu, Chang; Wu, Hao Bin; Wang, Gang; Dong, Qiang; Qiu, Jieshan; Eychmüller, Alexander; (David) Lou, Xiong Wen
<x xml:space="preserve">Abstract</x> A flexible film electrode is fabricated by growing TiO2(B) nanosheets on electrospun carbon nanofiber fabric. The hybrid electrode exhibits remarkable electrochemical performance with high reversible capacity, excellent rate capability, and ultralong cycle life for thousands of cycles, which makes it highly attractive for high‐power flexible lithium‐ion batteries. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>